2010
DOI: 10.1159/000322340
|View full text |Cite
|
Sign up to set email alerts
|

<i>Syzygium cumini</i> Extract Decrease Adenosine Deaminase, 5′Nucleotidase Activities and Oxidative Damage in Platelets of Diabetic Patients

Abstract: Diabetes mellitus, a chronic metabolic disorder, has assumed epidemic proportions and its long-term complications can have devastating consequences. The oxidative stress in diabetes was greatly increased due to prolonged exposure to hyperglycemia and impairment of oxidant/antioxidant equilibrium. Syzygium cumini is being widely used to treat diabetes by the traditional practitioners over many centuries. Adenosine deaminase (ADA) and 5′-Nucleotidase (5′NT) are enzymes of purine nucleoside metabolism that play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…The activity of both NTPDase and 5′-nucleotidase of platelets (and synaptosomes) showed increased activity in alloxan-induced diabetes [101, 102]. Adenosine deaminase and 5′-nucleotidase activities were higher in platelets in diabetic patients than control subjects [103]. In erythrocytes, ATP concentration is influenced by insulin levels in plasma [104], but there is impairment of ATP release from human erythrocytes in T2D, which may contribute to the vascular disease [105].…”
Section: Purinergic Signalling In Diabetesmentioning
confidence: 99%
“…The activity of both NTPDase and 5′-nucleotidase of platelets (and synaptosomes) showed increased activity in alloxan-induced diabetes [101, 102]. Adenosine deaminase and 5′-nucleotidase activities were higher in platelets in diabetic patients than control subjects [103]. In erythrocytes, ATP concentration is influenced by insulin levels in plasma [104], but there is impairment of ATP release from human erythrocytes in T2D, which may contribute to the vascular disease [105].…”
Section: Purinergic Signalling In Diabetesmentioning
confidence: 99%
“…ADA is essential for the proliferation and differentiation of lymphoid cells (Bota et al, 2001) downregulating the biologic effects of adenosine in situ and playing a key role in normal immune function (Hong-Jun et al, 2011). Recently, we observed that the ADA activity was higher in hyperglycemia conditions (Fredholm, 2007;De Bona et al, 2010). However, the potential contribution of ADA activity in the development of diabetic condition has not been fully clarified.…”
Section: Introductionmentioning
confidence: 97%
“…Extracts of different parts of the plant possess a range of pharmacological properties such as hypoglycemic, antiallergic, anticancer, anti-inflammatory, antimicrobial and antiulcerogenic activities, and cardioprotective and hepatoprotective effects, supporting its traditional use [8,9]. Previous studies from our group have investigated the effects of S. cumini leaf extract on ADA activity in diabetic patients and in different cells exposed to hyperglycemic conditions in vitro [4,7,[10][11][12][13]. Nonetheless, as there is paucity of data evaluating the properties of S. cumini seeds on ADArelated changes caused by DM, including the validated antidiabetic effects of the ASc on the short-term complications of DM, this study was aimed at evaluating the effect of the use of the ASc on ADA activity and on biochemical and histopathological parameters in a short-term rat model of diabetes induced by streptozotocin (STZ).…”
Section: Introductionmentioning
confidence: 98%